Volume 8: Polar and Arctic Sciences and Technology; Petroleum Technology 2018
DOI: 10.1115/omae2018-78707
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-Fluid Displacement for Primary Cementing in Deviated Washout Sections

Abstract: One of the most critical operations during well construction is the cementing procedure, where drilling fluid is displaced by cement, normally with one or more spacer fluids in between. Due to the curing nature of the cement slurry there will be only one opportunity to cement the well properly. Although one for top hole cases can fill cement in from the top in a remedial operation, this possibility cannot fully compensate for a non-optimal initial cement job. Furthermore, it cannot be applied to other well sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Conductivity can give more local information, e.g. an azimuthal distribution of displacement efficiency as in Tehrani et al (1992), or by the use of multiple axial banks of probes as in Lund et al (2018) and Skadsem et al (2019). However, typically the number of probes remains limited and spatio-temporal features of the flow remain obscured, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Conductivity can give more local information, e.g. an azimuthal distribution of displacement efficiency as in Tehrani et al (1992), or by the use of multiple axial banks of probes as in Lund et al (2018) and Skadsem et al (2019). However, typically the number of probes remains limited and spatio-temporal features of the flow remain obscured, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the suitability of the device that was applied in the displacement studies presented by Renteria et al [2], Tardy [4], Ytrehus et al [16], Lund et al [17,22] and Skadsem et al [18] has been verified. Note that some of these studies have been used in development of displacement software.…”
Section: Discussionmentioning
confidence: 88%
“…The experimental equipment presented here is designed for displacement measurements with non-hardening laboratory fluids, which is an applicable way of evaluating displacements experimentally [2,4,[16][17][18]. The two main approaches for monitoring the motion of the interface between the displaced and displacing fluids have been optical/visual and electrical resistance.…”
Section: Introductionmentioning
confidence: 99%
“…These studies generally stated that turbulent displacement flow is more efficient than the laminar displacement flow [17,18], and the increasing standoff causes a significant effect on the displacement flow of the fluids and cement placement [20][21][22]. In cases like washout sections, the effect of inner pipe eccentricity is not significant for displacement in the washout section [23]. Moreover, inclination reduction is beneficial for the displacement efficiency within the hole enlargement for both concentric and eccentric annuli and in the regular part of the annulus in front of the enlargement [22].…”
Section: Introductionmentioning
confidence: 99%
“…By using large-scale eccentric annular geometry, the importance of the rheological properties of the realistic non-Newtonian fluids for fluid flow and hole cleaning performance was expressed extensively [14][15][16], and the propagation of the fluid interfaces and displacement efficiency were characterized [24]. It was indicated that an enlarged irregular section, i.e., a washout causes an improvement in displacement in some scenarios in strongly inclined wellbores [17]; while being independent of the displacement efficiency in the washout itself, the presence of washouts may lead to poorer cement quality downstream of the washouts [23].…”
Section: Introductionmentioning
confidence: 99%